2022
DOI: 10.1038/s41598-021-04675-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal axial flow rice thresher feeding rate monitoring based on force sensing resistors

Abstract: The threshing unit is the main working unit of the combine harvester and plays an essential role in rice threshing efficiency, seed loss, and damage. Every thresher has its limitation for feeding, and when the feeding quantity exceeds the maximum rated amount, the thresher gets blocked, resulting in higher losses, low threshing efficiency, more power consumption, and combine overloading shutting down. This study constructed a longitudinal axial flow rice threshing platform, and a stress monitoring system for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In order to reveal the vibration intensity in the entire frequency domain, this paper analyzes the amplitudes corresponding to all frequency in the low frequency domain (0-80 Hz). Take the root mean square value (RMS), as shown in Equation (22).…”
Section: Signal Response and Failure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reveal the vibration intensity in the entire frequency domain, this paper analyzes the amplitudes corresponding to all frequency in the low frequency domain (0-80 Hz). Take the root mean square value (RMS), as shown in Equation (22).…”
Section: Signal Response and Failure Analysismentioning
confidence: 99%
“…Based on TCP/IP protocol, Si et al realized abnormal signal monitoring and alarm of threshing drum for data communication [19,20]. With the development of communication technology, many scholars have developed a fault monitoring and diagnosis platform for combine harvesters [21]; Abdeen et al used resistance sensors to design stress monitoring system of the top cover of the threshing drum is implemented and the real-time monitoring of the feeding amount of the threshing drum and the early warning function [22]; such monitoring systems usually include monitoring platforms such as rotational speed and torque, monitoring platforms such as clearance, fuel consumption and feed rate [23].…”
Section: Introductionmentioning
confidence: 99%
“…The unbalanced excitation of the threshing drum not only comes from the winding of straw, but also the state excitation signal of the continuous roller bearing used for threshing in the threshing drum device will cause the central trajectory of the central axis of the threshing drum to change [10]. In order to observe the change in the central trajectory more accurately, vibration changes on threshing cylinders are detected with a monitoring system [11]. In addition, relevant studies have shown that the wear rate of threshing drum can be reduced by changing suitable materials [12].…”
Section: Introductionmentioning
confidence: 99%